2021
DOI: 10.1073/pnas.2025452118
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution asymmetric structure of a Fab–virus complex reveals overlap with the receptor binding site

Abstract: Canine parvovirus is an important pathogen causing severe diseases in dogs, including acute hemorrhagic enteritis, myocarditis, and cerebellar disease. Overlap on the surface of parvovirus capsids between the antigenic epitope and the receptor binding site has contributed to cross-species transmission, giving rise to closely related variants. It has been shown that Mab 14 strongly binds and neutralizes canine but not feline parvovirus, suggesting this antigenic site also controls species-specific receptor bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…These structures were roughly spherical with angular edges. They appeared similar to virus capsids ( Goetschius et al, 2021 ; Vijayakrishnan et al, 2020 ), and so we call them virus-like capsids. Many contained discrete, globular densities in the lumen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These structures were roughly spherical with angular edges. They appeared similar to virus capsids ( Goetschius et al, 2021 ; Vijayakrishnan et al, 2020 ), and so we call them virus-like capsids. Many contained discrete, globular densities in the lumen ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work revealed the interactions between mAb Fab14 and FabE and CPV-2 capsids at high resolution (Fig. 1A and B) (33,34). Here, we determined the selective pressure impose by those antibodies and defined the subsequent emergence of escape mutations in antibody and receptor binding sites (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Mouse or rat monoclonal antibodies (mAb) prepared against FPV, CPV-2, or CPV-2a capsids recognize many positions on the capsid surface, and cryoEM analysis of the binding sites of eight different rodent IgGs showed that their footprints covered about 65% of the capsid surface (1,17). Near-atomic resolution structures of some of these antibodies bound to CPV capsids have been obtained and confirm that both the antibody heavy and light chain complementarity determining regions (CDRs) contact multiple surface loops from different VP2 (or VP1) subunits (33,34). Antigenic variation in CPV-and FPV-related viruses have frequently been observed during their natural evolution (35)(36)(37), and escape mutations are readily selected by the growth of viruses in the presence of the mAbs (38,39).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…A metadata file containing icosahedrally refined particle origins and orientations is required as input. The beta version of ISECC was used with cryoSPARC metadata files [ 17 , 26 ]. ISECC_subparticle_extract was used after icosahedral refinement to divide each particle image into subparticles [ 17 ].…”
Section: Methodsmentioning
confidence: 99%